Prevalence of Malabsorption Leads to Celiac Disease among the Libyan Population: Pathological and Therapeutic Rules - Abdalla Hamed; Sulaiman Essa; Yousef Hasen; Subhia Shaglabow; Malak Hamed (AlQalam Journal of Medical and Applied Sciences, 2025)
Celiac disease is a chronic autoimmune disorder that primarily impacts the small intestine. It arises from the consumption of gluten in individuals who possess specific genetic markers, namely the HLA-DQ2 or HLA-DQ8 antigens, leading to mucosal inflammation and villous atrophy, which ultimately results in malabsorption. Diagnosis is typically achieved through various diagnostic methods, including a small bowel biopsy. The global prevalence of CD in the general population is approximately 1%, with rates in North Africa ranging from 0.5% to 1%, aligning with global averages. Recent findings indicate that celiac disease is not necessarily less prevalent in certain regions but often goes undiagnosed. The cornerstone of treatment following a confirmed diagnosis is lifelong adherence to a gluten-free diet. This study aims to examine the prevalence of malabsorption associated with celiac disease in the Libyan population, along with its epidemiology, pathogenesis, clinical manifestations, diagnostic approaches, and current therapeutic strategies. Despite an anticipated rise in celiac disease cases in Africa due to enhanced disease awareness and diagnostic advancements, reports of celiac disease in North Africa, particularly Libya, remain scarce. This paper will present documented cases of celiac disease in Libya while summarizing key aspects. Additionally, we will discuss the epidemiology, diagnostic criteria, and treatment protocols for celiac disease in Libya.